EFEKTIVITAS SALEP DAUN SIRIH DAN MENIRAN TERHADAP PENURUNAN JUMLAH BAKTERI PADA SAPI PERAH PENDERITA MASTITIS SUB KLINIS - Zalizar, Lili (Jurnal Gamma, 2010)
The study aimed to examine the effectiveness of daun sirih (Piper betle leaf ) and meniran(Phyllanthus niruri) ointment to decrease the number of bacteria in milk of subclinical mastitis ofdairy cows have been conducted on a dairy farm in Pujon and in the Faculty of Agriculture-AnimalHusbandry Muhammadiyah University of Malang. Experiment has done with completely randomizeddesign and five treatments: group negative controls (given sterile Nacl), positive control (givenantiseptic iodine), Piper betle leaf ointment, Phyllanthus niruri ointment and mixed ointment (Piperbetle and Phyllanthus niruri) leaves mixed with a ratio 50 percent each herbal. Results showed thenumber of bacteria in group treated with herbal ointment fewer than the group without treatment.The number of bacteria on day 20 (end of study) decline of 90.35 percent in dairy cow with havePiper betle leaf ointment; 87.92 percent with meniran ointment and 98.86 percent of the grouphave mixed (Piper betle leaf and Phyllanthus niruri) ointment and the group receiving iodinereached 98.86 percent.